2015
DOI: 10.1093/annonc/mdv023
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms to predict survival and the risk for developing local or distant recurrence in patients with rectal cancer treated with optional short-term radiotherapy

Abstract: The developed nomograms can contribute to better individual risk prediction for LR, DM and OS for patients operated on rectal cancer. The practicality of the defined risk groups makes decision support in the consulting room feasible, assisting physicians to select patients for adjuvant therapy or intensified follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
3
46
1
Order By: Relevance
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…Their study had a large sample size (2795 cases) with external validation, and the results were accurate and reliable. There are other models [39,40] for predicting survival and recurrence in patients with rectal cancer. Nevertheless, there are no such prediction models combining genetic information with clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…22 Most frequently evaluated prognostic factors include those directly associated to the neoplasm per se, that is, morphologic, proteomic, genomic or epigenomic, while the patient's immune and nutritional status have been often overlooked. [6][7][8][9] There is an increasing evidence that systemic inflammation plays a critical role in carcinogenesis and the invasion or metastatic processes in CRC. 30 The tumor-associated inflammatory response has been recognized to exert a contradictory effect, enhancing tumorigenesis and progression, and actually aiding incipient neoplasms to acquire hallmark capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, more refined tools are needed to further increase their prognostic value. The Memorial Sloan-Kettering Cancer Center model, which was designed to predict the 5-and 10-year disease-free survival after curative resection in patients with colon cancer, or the European CanCer Organisation/European Society of Surgical Oncology nomograms predicting recurrence, distant metastases and OS, 8,9 have been important contributions to the field. Nonetheless, the baseline immunonutritional status of patients was not considered as part of most of the conceptual models supporting these tools or were only defined in specific subpopulations of patients with CRC or specific stage groupings, 6 even when inflammation has been widely recognized as the promoter of multiple hallmark functional components of cancer.…”
Section: Introductionmentioning
confidence: 99%